Vacation as a Public Health Resource: Toward a Wellness-Centered Tourism Design Approach. (September 2019) - Lehto, Xinran Y.; Lehto, Mark R.
In today's technology-driven configuration of work and life systems, wellness imbalances underscore the need for time away from sources of stress in the workplace, school, and other living scenarios. Increasingly, consumers are turning to vacation travel for health and wellness enhancement. The tourism and hospitality industries can design experiences and services that support optimal health and wellness outcomes for consumers. Drawing from interdisciplinary perspectives, this study revisits tourism as a personal health and wellness resource and discusses opportunities for better leveraging design factors in delivering, communicating, and sustaining health and wellness benefits of tourism. This article proposes a traveler wellness–centered design framework and highlights the important role of tourism and hospitality providers in safeguarding human health and wellness.